A multi-component fiber pretreatment liquid, a preparation process thereof and a hetero-shrinkage mixed filament
Patent Information
- Application Number
- CN202611186723.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
本申请中的预处理液,其中的选择性溶胀剂优先作用于无定形区比例较高、极性较强的高收缩聚酯纤维;协同渗透剂降低预处理液的界面张力并促进选择性溶胀剂向纤维内部迁移;链段活动调节剂有利于削弱高收缩聚酯纤维中链段间的极性作用,提高链段活动能力;液膜及相容性调节剂改善预处理液在丝束表面的附着和铺展均匀性;抗静电剂则减少纤维在连续处理过程中的静电积聚和丝束缠绕;由此,可使高收缩聚酯纤维与低收缩聚酯纤维形成不同程度的预处理响应,在后续相同热处理条件下扩大二者的收缩率差值,从而提高异收缩混纤丝的蓬松度、立体感和丰满手感,并改善连续加工稳定性;
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This application relates to the technical field of fiber treatment, and in particular to a multi-component fiber pretreatment liquid and its preparation process, as well as heteroshrunk mixed fibers. Background Technology
[0002] In the chemical industry, the application of multi-component fiber materials is becoming increasingly widespread, and heterogeneous shrinkage blended fibers, with their unique properties, have demonstrated significant value in industries such as textiles. With technological advancements, the performance requirements for heterogeneous shrinkage blended fibers are constantly increasing, especially their three-dimensional bulkiness and full hand feel. Current processes for preparing heterogeneous shrinkage blended fibers mostly employ uniform hot air or hot roller heating. This method applies heat simultaneously and evenly to all components of the blended fiber, ensuring that the heating process of high-shrinkage and low-shrinkage components is identical. Under this heating mode, it is difficult to precisely control the shrinkage of each component. Due to the uniform heating method, it is difficult to establish a sufficient difference in shrinkage rates between high-shrinkage and low-shrinkage components. This results in the final blended fiber having insufficient bulkiness, a stiff hand feel, and failing to simultaneously achieve sufficient shrinkage of the high-shrinkage component and dimensional stability of the low-shrinkage component. Summary of the Invention
[0003] To improve the bulk and feel of blended fibers, this application provides a multi-component fiber pretreatment liquid, its preparation process, and heterogeneous shrinkage blended fibers.
[0004] Firstly, this application provides a multi-component fiber pretreatment solution, which adopts the following technical solution: A multi-component fiber pretreatment solution, wherein the raw materials of the pretreatment solution include the following components in parts by weight: 8-15 parts of selective swelling agent, 5-10 parts of synergistic penetrant, 3-6 parts of chain segment activity regulator, 2-5 parts of liquid film and compatibility regulator, 1-3 parts of antistatic agent, and 61-81 parts of deionized water.
[0005] By adopting the above technical solution, the pretreatment solution is used to pretreat the blended fibers. The selective swelling agent preferentially acts on high-shrinkage polyester fibers with a higher proportion of amorphous regions and stronger polarity. The synergistic penetrant reduces the interfacial tension of the pretreatment solution and promotes the migration of the selective swelling agent into the fiber interior. The chain segment activity regulator helps to weaken the polar interaction between chain segments in high-shrinkage polyester fibers and improves the chain segment activity. The liquid film and compatibility regulator improves the adhesion and spreading uniformity of the pretreatment solution on the fiber bundle surface. The antistatic agent reduces the accumulation of static electricity and fiber bundle entanglement during continuous processing. As a result, high-shrinkage polyester fibers and low-shrinkage polyester fibers can form different degrees of pretreatment response, and under the same heat treatment conditions, the difference in their shrinkage rates can be increased, thereby improving the bulkiness, three-dimensionality, and full hand feel of the heterogeneous shrinkage blended fibers, and improving the stability of continuous processing.
[0006] In one specific implementation, the selective swelling agent comprises one or more of sodium dimethyl isophthalate-5-sulfonate, sodium dimethyl terephthalate-sulfonate, and sodium diethylene glycol isophthalate-5-sulfonate.
[0007] By adopting the above technical solution, the selective swelling agent contains both aromatic ester structures and sulfonate polar groups. The aromatic ester structure has a certain structural compatibility with the polyester molecular chain, which is beneficial for the selective swelling agent to migrate to the amorphous region of the polyester fiber. The sulfonate polar groups can improve its dispersion or solubility in the aqueous phase and enhance its interfacial interaction with high-shrinkage polyester fibers containing polar copolymer units. Through the above structural features, the selective swelling agent can be more easily enriched in high-shrinkage polyester fibers with low crystallinity and a high proportion of amorphous regions, while its effect on high-crystallinity, low-shrinkage polyester fibers is relatively weak. This improves the selectivity of the pretreatment solution for different polyester components and reduces the risk of over-plasticization of low-shrinkage polyester fibers.
[0008] In one specific implementation, the synergistic penetrant comprises diethylene glycol butyl ether.
[0009] By adopting the above technical solution, diethylene glycol butyl ether contains both hydrophilic ether bonds and hydrophobic butyl segments, which can play a compatibility and transfer role between the aqueous phase and the polyester fiber interface, reduce the surface tension of the pretreatment liquid and the wetting resistance of the fiber surface, and enable the pretreatment liquid to enter the fiber bundle more quickly. At the same time, diethylene glycol butyl ether can improve the distribution ability of selective swelling agent between the aqueous phase and the amorphous region of polyester, promote the diffusion of selective swelling agent from the fiber surface to the fiber interior, thereby shortening the impregnation treatment time and reducing the uneven treatment caused by the treatment liquid only staying on the fiber surface.
[0010] In one specific implementation, the chain activity regulator includes one or more of urea, thiourea, and guanidine hydrochloride.
[0011] By adopting the above technical solutions, the aforementioned substances all possess strong polarity and hydration properties, which can alter the association state of water molecules and polar auxiliaries in the pretreatment solution and promote the migration of polar components into the amorphous regions of high-shrinkage polyester fibers. Simultaneously, they can weaken the dipole interactions or local polar associations between polyester chain segments, thereby enhancing the mobility of amorphous chain segments under subsequent heating conditions. By improving the relaxation and deorientation capabilities of chain segments in high-shrinkage polyester fibers, the high-shrinkage components can achieve more complete shrinkage during subsequent heat treatment, while the low-shrinkage components are relatively less affected due to their higher crystallinity and fewer amorphous regions.
[0012] In one specific implementation, the liquid film and compatibility modifier include polyethylene glycol dimethyl ether, and the number average molecular weight of the polyethylene glycol dimethyl ether is 240 to 280.
[0013] By adopting the above technical solution, the polyethylene glycol dimethyl ether has a low molecular weight and good fluidity, which can improve the compatibility between organic components and aqueous phase in the pretreatment liquid, reduce local enrichment and stratification between different components, and help form a continuous and uniform liquid film. Its ether chain structure can also form a good compatibility system with diethylene glycol butyl ether and selective swelling agents, reducing the possibility of organic additives precipitating, oil spots or local concentration fluctuations during long-term cyclic use in the impregnation tank.
[0014] In one specific implementation, the antistatic agent comprises a potassium salt of an alkyl phosphate with a straight-chain C8-C12 hydrocarbon group.
[0015] By adopting the above technical solution, the potassium phosphate salt group in the antistatic agent has strong hydrophilicity, which can improve the hygroscopicity and ionic conductivity of the fiber surface, and make the static charge accumulated on the fiber surface dissipate in time; the linear C8-C12 alkyl group can form a moderate hydrophobic adsorption with the polyester fiber surface, improve the adhesion stability of the antistatic agent on the fiber surface, and can take into account both water dispersibility and fiber surface adsorption.
[0016] In one specific implementation scheme, the raw materials of the pretreatment liquid further include the following components in parts by weight: 1.5 to 2.5 parts of aromatic permeation carrier, 0.5 to 2.5 parts of cyclic carbonate plasticizer, and 0.1 to 0.3 parts of water-soluble cellulose ether.
[0017] By adopting the above technical solutions, the aromatic ring structure in the aromatic permeation carrier has good compatibility with the polyester chain segments and can be used as a selective swelling agent to enter the amorphous region of the polyester as a migration medium; the cyclic carbonate plasticizer has high polarity and strong dipole effect, which can further improve the free volume and chain segment mobility of the amorphous region of the polyester; the water-soluble cellulose ether can form a certain aqueous network structure, improving the low shear viscosity and static stability of the pretreatment solution.
[0018] In one specific implementation, the aromatic permeation carrier is composed of 2-phenoxyethanol and benzyl alcohol in a mass ratio of 1:(0.1-0.3); the cyclic carbonate plasticizer is composed of propylene carbonate and ethylene carbonate in a mass ratio of (1-3):1.
[0019] By adopting the above technical solution, 2-phenoxyethanol contains benzene rings, ether bonds, and hydroxyl groups, which have good compatibility with polyester segments and a relatively high boiling point, providing continuous penetration and carrier effects; benzyl alcohol has a small molecular size and a fast diffusion rate, which can quickly wet the amorphous region of polyester in the early stage of impregnation; after the two are compounded at a ratio of 1:(0.1-0.3), benzyl alcohol penetrates first and expands the migration channels of organic additives, and 2-phenoxyethanol then continuously enters the amorphous region, so that the pretreatment solution has both a fast initial penetration rate and a relatively stable subsequent plasticizing ability; propylene carbonate is liquid at room temperature, with good fluidity and solubility, which facilitates the formation of a uniform organic carrier phase; ethylene carbonate has high polarity and a strong plasticizing promoting effect on polyester segments, but its fluidity at room temperature is relatively weak; after the two are compounded at a ratio of (1-3):1, propylene carbonate can improve the dispersion and migration ability of ethylene carbonate in the pretreatment solution, while ethylene carbonate can enhance the polar effect and segment activity promotion effect of the composite plasticizer on the amorphous region of high shrinkage polyester.
[0020] Secondly, the preparation process of the multi-component fiber pretreatment liquid provided in this application adopts the following technical solution: A process for preparing a multi-component fiber pretreatment solution includes the following steps: Preparation of aqueous phase mixture: The first part of deionized water, which accounts for 50% to 70% of the total mass of deionized water, is heated to 50 to 65°C. Selective swelling agent and chain segment activity regulator are added sequentially under stirring conditions of 300 to 700 r / min. Stirring is continued for 20 to 40 min to obtain aqueous phase mixture. Dispersion preparation: Under shear conditions of 1500-4000 r / min, the synergistic penetrant was added to the aqueous phase mixture for 10-25 min, sheared and dispersed for 10-30 min, and then subjected to high-pressure homogenization 1-3 times under a homogenization pressure of 30-60 MPa to obtain the dispersion. Preparation of the mixture: Cool the dispersion to 30-40℃, add the liquid film, compatibility modifier and antistatic agent under stirring conditions of 200-500r / min, stir for 20-40min, and then add the remaining deionized water to obtain the mixture; Post-treatment: The pH of the mixture is adjusted to 5.5-6.8 using an acidic pH adjuster, filtered through a 100-200 mesh filter, and degassed under a vacuum of -0.04-0.08 MPa for 5-15 minutes to obtain a multi-component fiber pretreatment solution.
[0021] By adopting the above technical solution, the process sequence of aqueous phase mixing, premixing, high-speed shearing, high-pressure homogenization, low-temperature feeding, pH adjustment, filtration and vacuum degassing is limited, thereby improving the dispersion stability and batch consistency of the pretreated liquid. This results in a multi-component fiber pretreated liquid with uniform composition, small particle size, stable storage, less foam, and suitable for continuous recycling.
[0022] Thirdly, the heteroshrunk blended fiber provided in this application adopts the following technical solution: A heteroshrunk fiber blend, the preparation method of the heteroshrunk fiber blend includes the following steps: Impregnation: The blended filaments, including high-shrinkage polyester fibers and low-shrinkage polyester fibers, are placed in the multi-component fiber pretreatment solution and impregnated at 25-40°C for 8-40 seconds to obtain impregnated blended filaments. Pulping treatment: The impregnated blended fibers are subjected to pulping treatment to achieve a pulping residue of 25% to 60%, thus obtaining pulping blended fibers. Preheating treatment: The filaments of the filaments are preheated at 60-75℃ for 15-35s, and then pre-dried at 90-115℃ for 20-50s to reduce the moisture content of the filaments to below 2% to obtain pre-dried filaments. Heat treatment: The pre-dried blended fibers are sequentially passed through a first heat treatment zone and a second heat treatment zone to obtain heat-treated blended fibers. The temperature in the first heat treatment zone is 155–195℃, the residence time is 2–10 s, the overfeed rate of the blended fibers in the first heat treatment zone is 10%–20%, and the fiber tension is 0.02–0.10 cN / dtex. The temperature in the second heat treatment zone is 120–140℃, the residence time is 3–25 s, the overfeed rate of the blended fibers in the second heat treatment zone is 2%–8%, and the fiber tension is 0.05–0.15 cN / dtex. Isothermal length treatment: The heat-treated blended fibers are subjected to isothermal length treatment at 100-140℃ to obtain the crude product; Post-treatment: The crude product is washed with deionized water at 50-70℃ for 20-60 seconds, dried at 80-100℃, and cooled to below 35℃ to obtain hetero-shrinkage blended fibers.
[0023] By adopting the above technical solution, the pretreatment liquid impregnation, rolling, staged preheating, dual-temperature zone heat treatment, constant temperature and length setting, cleaning and drying and cooling are combined to make the selective action of the pretreatment liquid match the differential thermal response of high and low shrinkage components. This allows the selective pretreatment of high shrinkage polyester fibers, internal migration of the carrier, low-tension heat shrinkage and structural shaping to occur continuously, while the low shrinkage polyester fibers remain relatively stable, resulting in heterogeneous shrinkage blended fibers with a good hand feel.
[0024] In summary, this application includes at least one of the following beneficial technical effects: The pretreatment liquid in this application contains a selective swelling agent that preferentially acts on high-shrinkage polyester fibers with a high proportion of amorphous regions and strong polarity; a synergistic penetrant that reduces the interfacial tension of the pretreatment liquid and promotes the migration of the selective swelling agent into the fiber interior; a chain segment activity regulator that helps to weaken the polar interaction between chain segments in high-shrinkage polyester fibers and improves chain segment activity; a liquid film and compatibility regulator that improves the adhesion and spreading uniformity of the pretreatment liquid on the fiber tow surface; and an antistatic agent that reduces static electricity accumulation and fiber tow entanglement during continuous processing. As a result, high-shrinkage polyester fibers and low-shrinkage polyester fibers can form different degrees of pretreatment response, thereby increasing the difference in shrinkage rates between the two under the same subsequent heat treatment conditions, thus improving the bulkiness, three-dimensionality, and full hand feel of the heterogeneous shrinkage blended fibers, and improving the stability of continuous processing. The process described in this application limits the sequence of aqueous phase mixing, premixing, high-speed shearing, high-pressure homogenization, low-temperature feeding, pH adjustment, filtration and vacuum degassing, thereby improving the dispersion stability and batch consistency of the pretreated liquid. This process can produce a multi-component fiber pretreated liquid with uniform composition, small particle size, stable storage, less foam, and suitable for continuous recycling. The heteroshrunk blended fibers in this application combine pretreatment liquid impregnation, liquid rolling, staged preheating, dual-temperature zone heat treatment, constant temperature length setting, cleaning and drying, and cooling during the preparation process. This allows the selective action of the pretreatment liquid to be combined with the differential thermal response of the high and low shrinkage components, enabling the selective pretreatment of high shrinkage polyester fibers, internal migration of the carrier, low-tension heat shrinkage, and structural shaping to occur continuously, while the low shrinkage polyester fibers remain relatively stable, thus improving the hand feel. Detailed Implementation
[0025] The present application will be further described in detail below with reference to the embodiments.
[0026] All raw materials used in the examples are commercially available. Specifically, polyethylene glycol dimethyl ether is Sigma-Aldrich 445878; potassium alkyl phosphate salt has CAS number 39322-78-6; the acidic pH adjuster is glacial acetic acid; and the water-soluble cellulose ether is hydroxyethyl cellulose. Example
[0027] Example 1 Example 1 provides a process for preparing a multi-component fiber pretreatment solution, including the following steps: Preparation of aqueous phase mixture: 50 kg of deionized water was heated to 58 °C, and 8 kg of selective swelling agent and 3 kg of chain segment activity regulator were added sequentially under stirring at 500 r / min. The mixture was stirred for 30 min to obtain an aqueous phase mixture. The selective swelling agent was sodium dimethyl isophthalate-5-sulfonate, and the chain segment activity regulator was urea. Dispersion preparation: Under shear conditions of 2700 r / min, 5 kg of synergistic penetrant was added to the aqueous phase mixture for 15 min, followed by shear dispersion for 20 min. Then, the mixture was subjected to two high-pressure homogenizations at a homogenization pressure of 45 MPa to obtain the dispersion. The synergistic penetrant was diethylene glycol butyl ether. Preparation of the mixture: The dispersion was cooled to 35℃, and 2 kg of liquid film, compatibility modifier and 1 kg of antistatic agent were added under stirring at 350 r / min. The mixture was stirred for 30 min, and then 31 kg of deionized water was added to obtain the mixture. The liquid film and compatibility modifier was polyethylene glycol dimethyl ether; the antistatic agent was potassium alkyl phosphate. Post-treatment: The pH of the mixture was adjusted to 6.0 using an acidic pH adjuster, filtered through a 150-mesh filter, and degassed under a vacuum of -0.06 MPa for 10 minutes to obtain a multi-component fiber pretreatment solution.
[0028] Example 2 The difference between Example 2 and Example 1 lies in the preparation of the aqueous mixture: 42 kg of deionized water was heated to 58°C, and 11.5 kg of selective swelling agent and 4.5 kg of chain segment activity regulator were added sequentially under stirring at 500 r / min. The mixture was stirred for another 30 min to obtain the aqueous mixture. The selective swelling agent was sodium dimethyl isophthalate-5-sulfonate, and the chain segment activity regulator was urea. Dispersion preparation: Under shear conditions of 2700 r / min, 7.5 kg of synergistic penetrant was added to the aqueous phase mixture for 15 min, followed by shear dispersion for 20 min. Then, the mixture was subjected to two high-pressure homogenizations at a homogenization pressure of 45 MPa to obtain the dispersion. The synergistic penetrant was diethylene glycol butyl ether. Preparation of the mixture: The dispersion was cooled to 35°C, and 3.5 kg of liquid film, compatibility modifier and 2 kg of antistatic agent were added under stirring at 350 r / min. The mixture was stirred for 30 min, and then 29 kg of deionized water was added to obtain the mixture. The liquid film and compatibility modifier was polyethylene glycol dimethyl ether; the antistatic agent was potassium alkyl phosphate salt; the remaining steps were the same as in Example 1.
[0029] Example 3 The difference between Example 3 and Example 1 lies in the preparation of the aqueous mixture: 36 kg of deionized water was heated to 58°C, and 15 kg of selective swelling agent and 6 kg of chain segment activity regulator were added sequentially under stirring at 500 r / min. The mixture was stirred for another 30 min to obtain the aqueous mixture. The selective swelling agent was sodium dimethyl isophthalate-5-sulfonate, and the chain segment activity regulator was urea. Dispersion preparation: Under shear conditions of 2700 r / min, 10 kg of synergistic penetrant was added to the aqueous phase mixture for 15 min, followed by shear dispersion for 20 min. Then, the mixture was subjected to two high-pressure homogenizations at a homogenization pressure of 45 MPa to obtain the dispersion. The synergistic penetrant was diethylene glycol butyl ether. Preparation of the mixture: The dispersion was cooled to 35°C, and 5 kg of liquid film, compatibility modifier and 3 kg of antistatic agent were added under stirring at 350 r / min. The mixture was stirred for 30 min, and then 25 kg of deionized water was added to obtain the mixture. The liquid film and compatibility modifier were polyethylene glycol dimethyl ether; the antistatic agent was potassium alkyl phosphate; the remaining steps were the same as in Example 1.
[0030] Example 4 The difference between Example 4 and Example 2 lies in the preparation of the aqueous mixture: 42 kg of deionized water was heated to 58°C, and 11.5 kg of selective swelling agent and 4.5 kg of chain segment activity regulator were added sequentially under stirring at 500 r / min. The mixture was stirred for another 30 min to obtain the aqueous mixture. The selective swelling agent was sodium dimethyl isophthalate-5-sulfonate, and the chain segment activity regulator was urea. Dispersion preparation: 7.5 kg of synergistic penetrant, 2 kg of aromatic penetrant carrier, and 1.5 kg of cyclic carbonate plasticizer were first mixed at 42 °C for 12 min, and then added to the aqueous phase mixture under shear conditions of 2700 r / min for 15 min. Shear dispersion was carried out for 20 min, followed by two high-pressure homogenizations at a homogenization pressure of 45 MPa to obtain the dispersion. The synergistic penetrant was diethylene glycol butyl ether; the aromatic penetrant carrier was composed of 2-phenoxyethanol and benzyl alcohol in a mass ratio of 1:0.2; and the cyclic carbonate plasticizer was composed of propylene carbonate and ethylene carbonate in a mass ratio of 2:1. Preparation of the mixture: The dispersion was cooled to 35°C, and 3.5 kg of liquid film, compatibility modifier and 2 kg of antistatic agent were added under stirring at 350 r / min. The mixture was stirred for 30 min, and then 25.5 kg of deionized water was added to obtain the mixture. The liquid film and compatibility modifier was polyethylene glycol dimethyl ether; the antistatic agent was potassium alkyl phosphate salt; the remaining steps were the same as in Example 2.
[0031] Example 5 The difference between Example 5 and Example 4 is that the aromatic permeation carrier is 2-phenoxyethanol; the remaining steps are the same as in Example 4.
[0032] Example 6 The difference between Example 6 and Example 4 is that the aromatic permeation carrier is benzyl alcohol; the remaining steps are the same as in Example 4.
[0033] Example 7 The difference between Example 7 and Example 4 is that the cyclic carbonate plasticizer is propylene carbonate; the remaining steps are the same as in Example 4.
[0034] Example 8 The difference between Example 8 and Example 4 is that the cyclic carbonate plasticizer is ethylene carbonate; the remaining steps are the same as in Example 4.
[0035] Example 9 The difference between Example 9 and Example 4 lies in the preparation of the mixture: 25.3 kg of deionized water was heated to 60°C, and 0.2 kg of water-soluble cellulose ether was slowly added while stirring at 650 r / min. The mixture was stirred for 45 min and then cooled to 35°C to obtain a water-soluble cellulose ether pre-dispersion. The dispersion was then cooled to 35°C, and 3.5 kg of liquid film and compatibility modifier, water-soluble cellulose ether pre-dispersion, and 2 kg of antistatic agent were added while stirring at 350 r / min. The mixture was stirred for 30 min to obtain the mixture. The liquid film and compatibility modifier was polyethylene glycol dimethyl ether, and the antistatic agent was potassium alkyl phosphate. The remaining steps were the same as in Example 4. Comparative Example
[0036] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the dispersion was prepared as follows: 5 kg of synergistic penetrant was added to 61 kg of deionized water under a shearing condition of 2700 r / min for 15 min, followed by shearing dispersion for 20 min, and then high-pressure homogenization was performed twice under a homogenizing pressure of 45 MPa to obtain the dispersion; wherein the synergistic penetrant was diethylene glycol butyl ether. Preparation of the mixture: The dispersion was cooled to 35°C, and 2 kg of liquid film, compatibility modifier and 1 kg of antistatic agent were added under stirring at 350 r / min. The mixture was stirred for 30 min, and then 31 kg of deionized water was added to obtain the mixture. The liquid film and compatibility modifier was polyethylene glycol dimethyl ether; the antistatic agent was potassium alkyl phosphate salt; the remaining steps were the same as in Example 1.
[0037] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the aqueous phase mixture was prepared as follows: 50 kg of deionized water was heated to 58 °C, and 11 kg of selective swelling agent was added under stirring at 500 r / min. The mixture was stirred for another 30 min to obtain the aqueous phase mixture. The selective swelling agent was sodium dimethyl isophthalate-5-sulfonate. The remaining steps were the same as in Example 1.
[0038] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the aqueous mixture was prepared as follows: 50 kg of deionized water was heated to 58°C, and 11 kg of chain segment activity regulator was added under stirring at 500 r / min. The mixture was stirred for another 30 min to obtain the aqueous mixture. The chain segment activity regulator was urea. The remaining steps were the same as in Example 1. Application examples
[0039] Application Example 1 Application Example 1 provides a method for preparing heteroshrunk blended fibers, comprising the following steps: Impregnation: The blended filaments, including high-shrinkage polyester fibers and low-shrinkage polyester fibers, were placed in the multi-component fiber pretreatment solution of Example 1 and impregnated at 30°C for 12 seconds while being subjected to ultrasonic vibration at 40 kHz to obtain impregnated blended filaments; wherein the high-shrinkage component of the blended filaments is polyester fiber with an amorphous region ratio of more than 60% and a main chain containing sulfonic acid group grafting sites, and the low-shrinkage component is polyester fiber with a crystallinity of more than 55%; the impregnation step is to use an impregnation tank equipped with a guide roller group and a bottom ultrasonic vibrating plate, the blended filaments pass through the impregnation tank at a speed of 65 m / min, and the ultrasonic vibrating plate continuously oscillates at a frequency of 40 kHz to promote the penetration of the pretreatment solution. Pulping treatment: The impregnated blended fibers are subjected to pulping treatment to achieve a pulping residue of 52%, thus obtaining pulping-treated blended fibers. Preheating treatment: The filaments of the filaments are preheated at 67°C for 25 seconds and then pre-dried at 95°C for 40 seconds to reduce the moisture content of the filaments to below 2% to obtain pre-dried filaments. Heat treatment: The pre-dried blended fibers are sequentially passed through a first heat treatment zone and a second heat treatment zone to obtain heat-treated blended fibers. The temperature of the first heat treatment zone is 185℃, the residence time is 3s, the overfeed rate of the blended fibers in the first heat treatment zone is 15%, and the fiber tension is 0.06cN / dtex. The temperature of the second heat treatment zone is 128℃, the residence time is 4s, the overfeed rate of the blended fibers in the second heat treatment zone is 5%, and the fiber tension is 0.1cN / dtex. Constant temperature and length treatment: The heat-treated blended fibers are subjected to constant temperature and length treatment at 105℃ for 12s to obtain the crude product; Post-processing: The crude product was washed with deionized water at 60℃ for 40 seconds, dried at 90℃, and cooled to below 35℃ to obtain hetero-shrinkage blended fibers.
[0040] Application Example 2 The difference between Application Example 2 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Example 2, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0041] Application Example 3 The difference between Application Example 3 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Example 3, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0042] Application Example 4 The difference between Application Example 4 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Example 4, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0043] Application Example 5 The difference between Application Example 5 and Application Example 1 is that, in the impregnation process, the blended filaments, including high-shrinkage polyester fibers and low-shrinkage polyester fibers, are placed in the multi-component fiber pretreatment solution in Example 5 and impregnated at 30°C for 12 seconds while being subjected to ultrasonic vibration at 40 kHz to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0044] Application Example 6 The difference between Application Example 6 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Example 6, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0045] Application Example 7 The difference between Application Example 7 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Example 7, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0046] Application Example 8 The difference between Application Example 8 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Example 8, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0047] Application Example 9 The difference between Application Example 9 and Application Example 1 is that, in the impregnation process, a blend of high-shrinkage polyester fibers and low-shrinkage polyester fibers is placed in the multi-component fiber pretreatment solution of Example 9 and impregnated at 30°C for 12 seconds while being subjected to ultrasonic vibration at 40 kHz to obtain impregnated blended fibers; the remaining steps are consistent with those of Application Example 1. Comparative Application Examples
[0048] Comparative Application Example 1 The difference between Comparative Example 1 and Application Example 1 is that, impregnation: the blended filaments including high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution in Comparative Example 1, impregnated at 30°C for 12s, and simultaneously subjected to 40kHz ultrasonic vibration to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0049] Comparative Application Example 2 The difference between Application Example 2 and Application Example 1 is that, in the impregnation process, the blended filaments, including high-shrinkage polyester fibers and low-shrinkage polyester fibers, are placed in the multi-component fiber pretreatment solution in Comparative Example 2 and impregnated at 30°C for 12 seconds while being subjected to ultrasonic vibration at 40 kHz to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1.
[0050] Comparative Application Example 3 The difference between Application Example 3 and Application Example 1 is that, in the impregnation process, the blended filaments, including high-shrinkage polyester fibers and low-shrinkage polyester fibers, are placed in the multi-component fiber pretreatment solution in Comparative Example 3 and impregnated at 30°C for 12 seconds while being subjected to ultrasonic vibration at 40 kHz to obtain impregnated blended filaments; the remaining steps are consistent with Application Example 1. Performance testing experiment
[0051] The heteroshrunk blended fibers obtained from the various application examples and the comparative application examples were conditioned for 24 hours under tension-free conditions in an environment with a temperature of 20±2℃ and a relative humidity of 65±4%. All performance tests were conducted in the above environment, with no fewer than 5 parallel samples per test group, and the arithmetic mean was taken as the test result. The conditioning conditions for the samples were set in accordance with the current GB / T 6529—2008 "Standard Atmospheres for Conditioning and Testing of Textiles".
[0052] Shrinkage difference: The test was conducted according to GB / T 6505—2017 "Test Method for Heat Shrinkage Rate of Chemical Fiber Filaments". Since the heterogeneous shrinkage blended yarn contains both high-shrinkage polyester fibers and low-shrinkage polyester fibers, in order to accurately determine the shrinkage difference between the two components, accompanying samples were taken from the same batch of high-shrinkage polyester fibers and low-shrinkage polyester fibers before blending. The two accompanying samples were subjected to the same pretreatment liquid immersion, sizing, preheating, pre-drying, first heat treatment zone, second heat treatment zone, isothermal length setting, cleaning and drying treatment as in the corresponding application example. Under the pre-tension specified in the standard, the initial lengths of high-shrinkage polyester fibers and low-shrinkage polyester fibers before treatment were measured and denoted as LH0 and LL0, respectively; the lengths after the same treatment and humidification were measured and denoted as LH1 and LL1, respectively; the shrinkage rate of high-shrinkage polyester fibers was calculated according to the following formula: SH=(LH0-LH1) / LH0*100%; the shrinkage rate of low-shrinkage polyester fibers was calculated according to the following formula: SL=(LL0-LL1) / LL0*100%; the difference in shrinkage rate ΔS=absolute value of SH-SL; each sample was tested 10 times and the average value was taken. The greater the difference in shrinkage rate, the more obvious the differential regulation effect of the pretreatment liquid on the high-shrinkage component and the low-shrinkage component.
[0053] Loft: The sample conditioning and sampling process can refer to the sample treatment principles in GB / T 6506—2017 "Test Method for Curling Properties of Synthetic Fiber Textured Yarns"; the specific test method is as follows: Randomly sample 5.00±0.01g of heteroshrunk blended yarn from each test sample; uniformly place the sample into a smooth-walled cylindrical measuring cylinder without applying additional stretching, avoiding artificial compaction and local entanglement; place a circular pressure plate that matches the inner diameter of the measuring cylinder above the sample and apply a pressure of 0.50±0.02kPa to the sample; after holding the pressure for 60s, read the volume V occupied by the sample in the measuring cylinder; test each sample 5 times, replacing it with a new sample each time. The volume loft of heteroshrunk blended yarn is calculated according to the following formula: B=V / m, where V is the volume occupied by the sample under the specified pressure, in cm³; m is the sample mass, in g. The greater the bulkiness, the larger the apparent volume occupied by the heterogeneous shrinkage blended fibers per unit mass, and the more obvious the bending, looping and spatial misalignment structures formed by the high and low shrinkage components.
[0054] Hand feel: Referring to FZ / T 01166—2022 "Textile Fabric Hand Feel Testing and Evaluation Method - Multi-index Integrated Method", the heterogeneous shrinkage blended fibers prepared in each application example and the comparative application example were knitted into plain knitted fabrics using the same small-scale knitting machine. Each sample used the same needle number, loop length, yarn tension, and knitting density to prepare a sample with a size of not less than 20cm×20cm. The knitted samples were conditioned for 24 hours in an environment with a temperature of 20±2℃ and a relative humidity of 65±4%. The samples were randomly numbered, and 10 uniformly trained evaluators conducted hand feel evaluations without knowing the correspondence between the sample numbers. The evaluators scored the samples from three aspects: softness, fullness, and smoothness, with a maximum score of 5 points for each aspect. The scoring criteria are shown in Table 1. The comprehensive hand feel score given by a single evaluator was calculated according to the following formula: Hi=(Hi1+Hi2+Hi3) / 3, where Hi1 is the softness score, Hi2 is the fullness score, and Hi3 is the smoothness score. After removing the highest and lowest values from the overall hand feel scores of 10 evaluators, the arithmetic mean of the remaining 8 values is taken as the hand feel score for that sample. A higher hand feel score indicates better softness, fullness, and smoothness of the fabric made from the heterogeneous shrinkage blended yarns.
[0055] Table 1 Scoring Criteria
[0056] Table 2 Performance test results of heteroshrunk blended fibers
[0057] Combining Application Example 1 and Comparative Application Examples 1-3, the pretreatment solution used in Comparative Application Example 1, which lacks selective swelling agents and chain segment activity regulators, showed a shrinkage rate difference of only 7.4 percentage points. This indicates that relying solely on diethylene glycol butyl ether, polyethylene glycol dimethyl ether, and antistatic agents can only improve wetting, liquid film, and processing stability, but cannot sufficiently enhance the selective chain segment activity of high-shrinkage polyester fibers. Comparative Application Example 2, lacking chain segment activity regulators, although the selective swelling agent can have some effect on high-shrinkage polyester fibers, lacks the regulation of polar association state and the promotion of chain segment activity; therefore, its shrinkage rate difference and bulkiness are significantly lower than in Application Example 1. Comparative Application Example 3, lacking selective swelling agents, even with increased chain segment activity regulator dosage, struggles to preferentially enrich the effective components in the amorphous region of high-shrinkage polyester fibers, thus its performance is lower than that of Comparative Application Example 2. Combining Application Examples 1-3, Application Example 2 showed higher shrinkage rate difference, bulkiness, and hand feel compared to Application Example 1. This indicates that appropriately increasing the dosage of selective swelling agent, synergistic penetrating agent, and chain segment activity regulating component is beneficial for the migration of the pretreatment solution to the amorphous region of the high-shrinkage polyester fiber and improves its subsequent heat shrinkage capacity. Although the dosage of each basic component in Application Example 3 was higher than that in Application Example 2, its shrinkage rate difference, bulkiness, and hand feel were slightly lower. This suggests that when the dosage of selective swelling agent and synergistic penetrating agent is too high, some auxiliaries may simultaneously adhere to or migrate to the low-shrinkage polyester fiber, increasing the thermal relaxation degree of the low-shrinkage component and thus weakening the selective shrinkage difference between the two components.
[0058] Combining Application Examples 2 and 4, Application Example 4 further added an aromatic permeating carrier composed of 2-phenoxyethanol and benzyl alcohol, and a cyclic carbonate plasticizer composed of propylene carbonate and ethylene carbonate, based on Application Example 2. The shrinkage difference increased to 24.7 percentage points, the bulkiness increased to 27.6 cm³ / g, and the hand feel improved to 4.6 points. This indicates that the aromatic permeating carrier and the cyclic carbonate plasticizer can form a synergistic effect with the basic pretreatment system: the aromatic permeating carrier promotes the wetting and migration of the additives to the amorphous regions of the polyester, and the cyclic carbonate plasticizer further enhances the mobility of the chain segments in the amorphous regions, allowing the high-shrinkage component to shrink more fully under low tension and overfeed conditions.
[0059] In conjunction with Application Examples 4-6, Application Examples 5 and 6 used only 2-phenoxyethanol or benzyl alcohol as aromatic permeation carriers, respectively. Their performance was lower than that of Application Example 4, which used a combination of the two. This indicates that 2-phenoxyethanol has a more stable and sustained carrier effect. Benzyl alcohol has a smaller molecular size and a faster initial permeation rate, but its sustained plasticizing ability is relatively insufficient when used alone. When the two are combined in the prescribed ratio, both rapid initial wetting and sustained internal migration can be achieved, resulting in better performance than either component used alone.
[0060] Combining Application Examples 4, 7, and 8, Application Examples 7 and 8, which used only propylene carbonate or ethylene carbonate respectively, showed lower shrinkage, bulkiness, and hand feel compared to Application Example 4, which used a blend of both. Propylene carbonate exhibits better room temperature flowability and dispersibility, thus Application Example 7 demonstrates superior overall performance compared to Application Example 8. Ethylene carbonate, while highly polar, exhibits relatively insufficient room temperature dispersion and migration uniformity when used alone. When combined, propylene carbonate improves the dispersion and migration of ethylene carbonate, while ethylene carbonate enhances the polar effect of the composite plasticizer on the polyester segments, resulting in a better synergistic plasticizing effect in the blended system.
[0061] Combining Application Examples 4 and 9, Application Example 9, based on Application Example 4, further added 0.2 kg of hydroxyethyl cellulose. Its shrinkage rate difference, bulkiness, and hand feel reached 26.1 percentage points, 29.8 cm³ / g, and 4.8 points, respectively, representing the best results among all application examples. This indicates that water-soluble cellulose ethers can improve the low-shear viscosity and liquid film stability of the pretreatment solution, resulting in a more uniform distribution of aromatic permeating carriers and cyclic carbonate plasticizers in the inner and outer layers of the fiber bundle. It also reduces free liquid dripping after impregnation and localized aggregation of organic carriers. The uniform liquid state allows high-shrinkage polyester fibers to achieve more consistent plasticization and relaxation shrinkage effects, thereby further improving the bulkiness and hand feel of the blended fibers.
[0062] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A multi-component fiber pretreatment solution, characterized in that: The raw materials of the pretreatment liquid include the following components in parts by weight: 8-15 parts of selective swelling agent, 5-10 parts of synergistic penetrant, 3-6 parts of chain segment activity regulator, 2-5 parts of liquid film and compatibility regulator, 1-3 parts of antistatic agent, and 61-81 parts of deionized water.
2. The multi-component fiber pretreatment solution according to claim 1, characterized in that: The selective swelling agent includes one or more of sodium dimethyl isophthalate-5-sulfonate, sodium dimethyl terephthalate-5-sulfonate, and sodium diethylene glycol isophthalate-5-sulfonate.
3. The multi-component fiber pretreatment solution according to claim 1, characterized in that: The synergistic penetrant includes diethylene glycol butyl ether.
4. The multi-component fiber pretreatment solution according to claim 1, characterized in that: The chain segment activity regulator includes one or more of urea, thiourea, and guanidine hydrochloride.
5. The multi-component fiber pretreatment solution according to claim 1, characterized in that: The liquid film and compatibility modifier include polyethylene glycol dimethyl ether, and the number average molecular weight of the polyethylene glycol dimethyl ether is 240-280.
6. The multi-component fiber pretreatment solution according to claim 1, characterized in that: The antistatic agent includes potassium salts of alkyl phosphates with alkyl groups that are straight-chain C8-C12 hydrocarbon groups.
7. The multi-component fiber pretreatment solution according to claim 1, characterized in that: The raw materials of the pretreatment liquid also include the following components in parts by weight: 1.5 to 2.5 parts of aromatic permeation carrier, 0.5 to 2.5 parts of cyclic carbonate plasticizer, and 0.1 to 0.3 parts of water-soluble cellulose ether.
8. The multi-component fiber pretreatment solution according to claim 7, characterized in that: The aromatic permeation carrier is composed of 2-phenoxyethanol and benzyl alcohol in a mass ratio of 1:(0.1-0.3); the cyclic carbonate plasticizer is composed of propylene carbonate and ethylene carbonate in a mass ratio of (1-3):
1.
9. A preparation process for a multi-component fiber pretreatment solution as described in any one of claims 1-8, characterized in that: Includes the following steps: Preparation of aqueous phase mixture: The first part of deionized water, which accounts for 50% to 70% of the total mass of deionized water, is heated to 50 to 65°C. Selective swelling agent and chain segment activity regulator are added sequentially under stirring conditions of 300 to 700 r / min. Stirring is continued for 20 to 40 min to obtain aqueous phase mixture. Dispersion preparation: Under shear conditions of 1500-4000 r / min, the synergistic penetrant was added to the aqueous phase mixture for 10-25 min, sheared and dispersed for 10-30 min, and then subjected to high-pressure homogenization 1-3 times under a homogenization pressure of 30-60 MPa to obtain the dispersion. Preparation of the mixture: Cool the dispersion to 30-40℃, add the liquid film, compatibility modifier and antistatic agent under stirring conditions of 200-500r / min, stir for 20-40min, and then add the remaining deionized water to obtain the mixture; Post-treatment: The pH of the mixture is adjusted to 5.5-6.8 using an acidic pH adjuster, filtered through a 100-200 mesh filter, and degassed under a vacuum of -0.04-0.08 MPa for 5-15 minutes to obtain a multi-component fiber pretreatment solution.
10. A heteroshrunk blended fiber, characterized in that: The method for preparing the heteroshrunk blended fiber includes the following steps: Impregnation: The blended filaments comprising high-shrinkage polyester fibers and low-shrinkage polyester fibers are placed in the multi-component fiber pretreatment solution as described in any one of claims 1-8 and impregnated at 25-40°C for 8-40 seconds to obtain impregnated blended filaments. Pulping treatment: The impregnated blended fibers are subjected to pulping treatment to achieve a pulping residue of 25% to 60%, thus obtaining pulping blended fibers. Preheating treatment: The filaments of the filaments are preheated at 60-75℃ for 15-35s, and then pre-dried at 90-115℃ for 20-50s to reduce the moisture content of the filaments to below 2% to obtain pre-dried filaments. Heat treatment: The pre-dried blended fibers are sequentially passed through a first heat treatment zone and a second heat treatment zone to obtain heat-treated blended fibers. The temperature in the first heat treatment zone is 155–195℃, the residence time is 2–10 s, the overfeed rate of the blended fibers in the first heat treatment zone is 10%–20%, and the fiber tension is 0.02–0.10 cN / dtex. The temperature in the second heat treatment zone is 120–140℃, the residence time is 3–25 s, the overfeed rate of the blended fibers in the second heat treatment zone is 2%–8%, and the fiber tension is 0.05–0.15 cN / dtex. Isothermal length treatment: The heat-treated blended fibers are subjected to isothermal length treatment at 100-140℃ to obtain the crude product; Post-treatment: The crude product is washed with deionized water at 50-70℃ for 20-60 seconds, dried at 80-100℃, and cooled to below 35℃ to obtain hetero-shrinkage blended fibers.